Guide to the Senate - Pastrana, Reginald M.; Raval, Demaree J.B. (Pasay City Legislative Research Service, 1998)
Purpose: "...to provide a broad overview of the organization and composition of the Senate as well as its unique roles and functions. In particular, it also attempts to give insights on knowing fully how the senate works as an institution, essentially in matters of legislation and other non-legislation functions."
Content/s: Glossary of Legislative terms. History of the Senate. Seal of the Senate. The Mace of the Senate. The Gavel. Senate (Composition and Organization). Term of office. Privileges, Suspension and Disqualification. Senate (Powers and Functions). Legislative Process.
Keywords: Philippines. -- Congress. -- Senate -- Handbooks, manuals, etc